2022
DOI: 10.1097/tp.0000000000004033
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Percutaneous Kidney Allograft Biopsy: Systematic Review and Meta-analysis

Abstract: Background. Kidney biopsy is important to guide the management of allograft dysfunction but has a risk of complications. This review aimed to determine the incidence and risk factors of complications after kidney allograft biopsy. Methods. This is a systematic review and meta-analysis of randomized controlled trials, cohort studies, or case-control studies indexed on PubMed, Embase, Cochrane Central Register of Controlled Trials, World Health Organization International Clinical Trials Registry, and ClinicalT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
(111 reference statements)
0
13
0
Order By: Relevance
“…A recent meta-analysis analyzing 40,082 biopsies from 72 studies showed that the incidence of postbiopsy bleeding requiring transfusion and major complications were 0.31% and 0.89%, respectively. 21 Consequently, there are relentless interests in the radiology and transplant community to search for alternative imaging biomarkers for guiding clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis analyzing 40,082 biopsies from 72 studies showed that the incidence of postbiopsy bleeding requiring transfusion and major complications were 0.31% and 0.89%, respectively. 21 Consequently, there are relentless interests in the radiology and transplant community to search for alternative imaging biomarkers for guiding clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…This study result showed that serum creatinine could be used to aid in the differentiation of the UNNECESSARY group from the NECESSARY group with moderate AUC, high sensitivity but unacceptably low specificity, indicating that many patients who may not need allograft biopsy may eventually receive this invasive procedure if serum creatinine was used as the sole determinant for biopsy. A recent meta‐analysis analyzing 40,082 biopsies from 72 studies showed that the incidence of post‐biopsy bleeding requiring transfusion and major complications were 0.31% and 0.89%, respectively 21 . Consequently, there are relentless interests in the radiology and transplant community to search for alternative imaging biomarkers for guiding clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy, particularly in allograft injury, is thus prone to profound sampling error and high inter/intra‐observer variability 45,46 . In terms of biopsy risks and complications, recent meta‐analyses show that while risk of major complications (0.3% of patients with bleeding requiring intervention in native and transplant biopsy), or death is infinitesimal (1 in 1667 patients with native and 5 in 38,593 with transplanted kidneys), there are non‐negligible risks (perinephric hematoma in 11% of native and 1.63% of transplanted kidneys, macroscopic hematuria in 3.5% of native and 3.2% of transplant biopsies) 47–49 …”
Section: Renal Physiology and Pathophysiology—a Primer For Mr Scientistsmentioning
confidence: 99%
“…Small hemodynamically inconsequential AVF are often an incidental finding. 8 There are no clear guidelines for treatment of AVF. Some authors advocate "watchful waiting" for asymptomatic fistulas and intervention when renal function is threatened.…”
Section: Case #2mentioning
confidence: 99%